Solar UV Photooxidation as Pretreatment for Stripping Voltammetric Trace Metal Analysis in River Water - Woldemichael, Gelaneh; Tulu, Taffa; Flechsig, Gerd-Uwe (International Journal of Electrochemistry, 2011)
The application of solar ultraviolet radiation as sample pretreatment or preparation step in stripping voltammetric analysis of trace metals in presence of low levels of dissolved organic carbon (DOC) natural water samples (river water) was studied. River water samples were collected from downstream of Warnow river (Germany) and acidified to pH of 2±0.2 (by addition of 1 mL of ultrapure 65% HNO3 per liter sample). Furthermore, 100 μL/L of hydrogen peroxide solution (ultrapure, 30% H2O2) was added to the samples as photochemical reaction initiator. The samples were transferred to polyethylene terephthalate (PET) bottles and irradiated with solar radiation of UV-A intensity of 3.6 mW/m2 for six hours, and the concentrations of Zn, Cd, Pb, and Cu were determined by differential pulse anodic stripping voltammetry (DPASV). The comparison of the values with the results obtained for the original untreated sample and artificial UV-treated one proved that solar UV radiation can be applied to the digestion of dissolved organic carbon in trace metal analysis in natural waters like river water, lake waters, well waters, and so forth.